Quality of Life Study following Cytoreductive Surgery and Intraperitoneal Chemotherapy for Pseudomyxoma Peritonei including Redo Procedures. (28th July 2013) - Kirby, Rachel; Liauw, Winston; Zhao, Jing; Morris, David
Abstract : Background . Our aim was to evaluate the quality of life following cytoreductive surgery and intraperitoneal chemotherapy for pseudomyxoma peritonei. We also conducted an analysis of all patients who underwent CRS and HIPEC for pseudomyxoma peritonei from 1997 to 2012. Methods . We contacted 87 patients using the FACT C (version 4) quality of life questionnaire, and FACIT-TS-G (version 1) was also used. Results . A total of 63 patients (response rate 72%) were available for quality of life interview and analysis. The median time from surgery to questionnaire evaluation was 31 months (range 6–161 months). 62% were females with an average age of 54 years. 22% of the patients had over one cytoreductive surgical procedure. We analysed our patients postoperatively based on physical, functional, social, and emotional well being who reported favourable outcomes in all sections. Patients who had a single procedure had a significantly higher score (P = 0.016 ) in the additional concerns section of the questionnaire. The patients who had a single procedure had better gastrointestinal digestion in terms of bowel control, appetite, and food digestion and also body appearance scoring. Conclusions . 79% of the patients stated that they would undergo further cytoreductive surgery and that redo procedures do not result in a significantly worse quality of life.